Young Greenlanders in the urban space of Nuuk - Pedersen, Birgit (Études/Inuit/Studies)

(untitled) (Association Inuksiutiit Katimajiit Inc., 2008)
AbstractThis paper discusses young urban Greenlanders living in Nuuk, and how they depict themselves in selected lyrics and the feature film Eskimo Weekend. Although Greenland is moving along at many levels in a transition process between old and new life styles, it has left the younger generation in a kind of limbo. Compared to their parents’ generation, which was occupied in finding its place in a post-colonial nation-building context, young Greenlanders are more focused on their individual lives. During the 1990s, they tried in different ways to reach their parents and the politicians in order to make them comprehend the serious neglect many of the young people have suffered in their short lives. Through their songs, the popular Greenlandic Rap group Prussic asked adults to take children and young people seriously, to listen to them and most importantly, to raise them like “normal kids” being loved and cared for without parents’ abuse of drugs and alcohol. As seen in the film Eskimo Weekend, the young Greenlanders are fascinated with global tendencies, but at the same time, they are trying to find a balance between the idea of a lifestyle linked to tradition, and that of a lifestyle linked to modernity.